The Vastus Medialis Oblique: Vastus Lateralis Electromyographic Intensity Ratio During Squat with Hip Adduction in Athletes with and Without Patellofemoral Pain Syndrome - Farhad Reza-zadeh; Reza Rajabi; Nouroddin Karimi; Shirin A'ali; Aidin Vali-Zadeh (University of Social Welfare and Rehabilitation Sciences, 2012)
Objective: This study was designed to compare vastus medialis oblique (VMO): vastus lateralis longus (VLL) electromyographic intensity ratio during squat with hip adduction in athletes with and without patellofemoral pain syndrome (PFPS). Materials & Methods: In this non-experimental and case-control study, 16 male athletes with PFPS were selected purposefully and 16 healthy male athletes aged 18-30 years from national teams (Volleyball, Handball and Taekwondo) were matched based on variables such as weight, height, age, dominancy. All subjects selected based on inclusion and exclusion criteria. EMG activity of VMO and VLL muscles was recorded by surface electrodes with Telemetric EMG System at 15, 30 and 45 degrees of squat and VMO: VLL ratio was calculated. One way ANOVA was used to compare these muscles ratio between two groups. Results: The ratio of VMO: VLL in both groups with and without PFPS in almost all angles were lower than one. However, healthy athletes had lower ratios. Also, there were no significant differences in VMO: VLL ratio at various angles. Conclusion: It seems that sports activities prevent VMO weakening in athletes. However, VMO: VLL ratio in athletes with and without patellofemoral pain does not influence by this syndrome.